Gene Therapy for Treating Diabetes - Jing, Yuelin (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Diabetes has already been a worldwide issue.it is a type of chronic disease with a high risk and a high number of cases. The main symptom of diabetes is not only the spike in blood sugar after eating and the difficulty in lowering it, but the numerous complications are also noteworthy. Currently, traditional treatments for diabetes include controlling sugar intake in the diet and insulin injection therapy. However, traditional diabetes treatments are not ideal. This is mainly due to the fact that diabetes is difficult to treat at the root of the problem and can only be regulated in the long term, not cured. But gene therapy offers us the possibility of treating diabetes in the long term or even permanently. This essay primarily begins with the various pathogenic pathways behind type 1 and type 2 diabetes, summarizes and analyzes some existing diabetes gene therapies that have been theoretically analyzed and experimentally verified. The pros and cons are compared, and the advantages and disadvantages are analyzed. Type 1 diabetes treated with gene therapy involves inhibition of false attacks by immune cells, ectopic expression of insulin-encoding genes, and repair of insulin-encoding gene activity. For type 2 diabetes, gene therapy focuses on increasing the sensitivity of insulin receptor cells to the insulin molecule. Overall, there is a variety of research on treating diabetes through gene therapy, but it is still in the experimental stage. I expect clinical trials to be on the agenda soon.